Carbon-coated oxygen-vacancy-enriched hollow sphere H-CeO2-coated C-NC composite material as well as preparation method and application thereof

By using carbon-coated oxygen-rich hollow spheres H-CeO2@C-NC composite as a catalyst in lithium-sulfur batteries, the shortcomings of lithium-sulfur battery catalysts in high magnification and long cycle stability are solved, and lithium-sulfur battery cells are realized Excellent performance and stability.

CN119306243APending Publication Date: 2025-01-14SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411388913.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing lithium-sulfur battery catalysts cannot meet the strong adsorption and rapid conversion requirements of LiPSs at the same time, resulting in poor performance of lithium-sulfur batteries in high magnification and long cycle stability.

Method used

The H-CeO2@C-NC composite material of carbon-coated oxygen-rich vacancy hollow spheres is used as catalyst to synthesize cerium oxide CeO2 through Cu2O template, and the surface is coated with polydopamine and carbonization to form a composite material with rich oxygen vacancy. Improves electron and ions transfer, enhances catalytic activity and conductivity.

Benefits of technology

The excellent rate performance and good long cycle stability of lithium-sulfur batteries are achieved, which significantly improves the charge storage dynamics and catalytic activity, inhibits the shuttle effect of polysulfides, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306243A_ABST
    Figure CN119306243A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-coated oxygen-vacancy-enriched hollow sphere H-CeO2-coated C-NC composite material and a preparation method and application thereof.The method comprises the steps that 1, polyvinylpyrrolidone is dissolved in an ethanol solution, CeCl3. 7H2O is added, Cu2O is added after the CeCl3. 7H2O is dissolved, stirring is conducted at the room temperature, and a brick-red solution is obtained; step 2, dropwise adding a sodium thiosulfate solution into the brick red solution to obtain a faint yellow solution, stirring at room temperature, and then sequentially standing, aging, centrifuging, washing and vacuum drying to obtain light yellow hollow CeO2 powder; step 3, respectively taking the hollow CeO2 powder and dopamine hydrochloride, adding into a Tris buffer solution, uniformly stirring, and sequentially centrifuging, washing and vacuum drying to obtain a CeO2 composite material CeO2 (at) PDA coated with polydopamine; and step 4, placing the CeO2 (at) PDA in a tubular furnace, and performing high-temperature carbonization treatment in an argon atmosphere to obtain the carbon-coated oxygen-vacancy-rich hollow sphere H-CeO2 (at) C-NC composite material which can endow the Li-S battery with excellent rate capability and good long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and specifically is a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material, and a preparation method and application thereof. Background Art

[0002] Lithium-sulfur batteries (Li-S) have low cost, good environmental compatibility and 2600Wh kg -1 However, its practical application has been hindered by the slow redox kinetics caused by the poor reversible transformation of Li2S and the severe capacity decay caused by the shuttling behavior of soluble lithium polysulfides (LiPSs). Reducing liquid polysulfides to solid Li2S can contribute about 75% of the theoretical capacity. Therefore, it is crucial to develop efficient catalysts to accelerate the nucleation process of Li2S, i.e., Li2S4→Li2S and reduce the accumulation of S substances, so as to improve the capacity and cycle life of lithium-sulfur batteries.

[0003] Traditional catalysts usually cause Li2S to accumulate on the catalyst surface, resulting in blockage of active sites and deactivation of the catalyst. At the same time, the high activation energy barrier of the Li2S dissociation process (Li2S→LiS) further reduces the reaction kinetics. Metal oxides, such as TiO2, MnO2, In2O3, etc., usually contain Li2S in the oxidation state of O 2- The oxygen anions and strong polar surface can be used as polar sites to anchor LiPSs and eliminate the shuttle effect, but the advantage of high polarity is likely to be offset by the inherent poor electronic conductivity caused by the wide bandgap semiconductor characteristics; even worse, the slow LiPSs conversion ability will in turn aggravate the accumulation of insoluble Li2S, thereby passivating the catalyst; in addition, the high activation energy barrier for Li2S nucleation and dissociation will further deteriorate the electrochemical performance of Li-S batteries. Therefore, it is crucial to develop highly active and durable bidirectional catalysts with good activation centers that can both stably nucleate and effectively dissociate Li2S.

[0004] At present, increasing the number of active sites and creating a suitable electronic structure are considered to be effective methods to simultaneously achieve strong sulfur confinement and accelerate the conversion of LiPSs in Li-S batteries. Defect engineering is an ideal scheme to increase the number of active sites because defects can adjust surface properties and electron distribution. As common and key defect types, doping heteroatoms and anion vacancies can effectively adjust the electrocatalytic performance of catalysts at the atomic level, thereby accelerating redox kinetics and inhibiting the shuttle effect. For example, [J. Zhou, SW Sun, XC Zhou, XY Rao, XY Xu, Z. Zhang, ZD Pan, QC Wang, ZL Wang, YT Wu, WD Wagner, XB Guo, X. Liu, C. Wang, CH Lu, Y. Zhang, Defect engineering enables an advanced separator modification for high-performance lithium-sulfur batteries, Chemical Engineering Journal, 487 (2024) 150574.] reported a multifunctional oxygen-deficient titanium dioxide / N-doped mesoporous carbon nanocomposite (TiO 2-x @NMC), as an efficient polysulfide buffer and catalytic conversion medium, TiO 2-x The NMC-aided separator effectively inhibits the release of LiPSs through good adsorption and catalytic conversion to insoluble Li2S2 / Li2S, and in situ generates abundant oxygen vacancies (V) on confined TiO2 nanoparticles (NPs). O ), further promoting the redox chemistry of polysulfides and avoiding the accumulation and shuttling of LiPSs; [S.Cheng, J.Wang, SRDuan, J.Zhang, Q.Wang, Y.Zhang, LGLi, HTLiu, QBXiao, HZLin, Anionic oxygen vacancies in Nb2O 5-x / carbon hybrid host endow rapid catalytic behaviors for high-performance high arealloading lithium sulfur pouch cell, Chemical Engineering Journal, 417 (2021) 128172.] Niobium oxide nanoparticles with anionic oxygen vacancies (AOV-Nb2O) were developed and synthesized on highly conductive hierarchical porous nanocarbon. 5-x @HHPC), as a sulfur anchor and lithium ion accelerator, it was demonstrated that the catalyst with more oxygen vacancies has a stronger interaction ability with polysulfides, making the hybrid porous matrix have a stronger catalytic ability, promoting ion dynamics, reducing barriers, and promoting the precipitation of Li2S; [D. Zhang, T. F. Duan, Y. X. Luo, S. L. Li, W. Q. Zhang, Y. Q. He, K. Zhu, L. Huang, Y. Yang, R. Z. Yu, X. K. Yang, H. B. Shu, Y. Pei, X. Y. Wang, M. F. Chen, Oxygen Defect-Rich WO 3-x -W3N4 Mott-Schottky Heterojunctions Enabling Bidirectional Catalysis for Sulfur Cathode, Advanced Functional Materials, 33(42)(2023)2306578.] 3-x -W3N4 Mott-Schottky heterojunction acts as a highly efficient catalyst, and the synergistic effect between WO3 and W3N4 effectively promotes the smooth fixation-diffusion-conversion of LiPSs; in addition, oxygen vacancies can serve as active sites for adsorption and activation of adsorbed products, effectively suppressing carrier recombination and reducing the energy barrier of charge transfer. At the same time, the Mott-Schottky heterojunction with oxygen vacancies can act as an effective catalyst, and more importantly, it can satisfy the Sabatier principle for proper adsorption.

[0005] Although great progress has been made in the above research fields, the developed catalysts cannot simultaneously meet the requirements of "strong adsorption" and "fast conversion" for LiPSs, and cannot achieve the Li-S battery requirements of excellent rate capability (>4C) and cycle stability (>1000 cycles). Therefore, the rational design and engineering of new catalysts are still of great significance for the practical application of lithium-sulfur batteries. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material and a preparation method and application thereof. The prepared H-CeO2@C-NC composite material can give Li-S batteries excellent rate performance and good long-cycle stability.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material comprises the following steps:

[0009] Step 1: Dissolve 10-40 g of polyvinyl pyrrolidone in 600-800 mL of 50% ethanol solution, add 300-600 mg of CeCl3·7H2O, and after it is dissolved, add 300-600 mg of Cu2O, stir at room temperature, and obtain a brick red solution;

[0010] Step 2, 200-400 mL of 1M sodium thiosulfate solution was added dropwise to the brick-red solution to obtain a light yellow solution, which was stirred at room temperature, and then allowed to stand for aging, centrifuged, washed and vacuum dried in sequence to obtain a light yellow hollow CeO2 powder;

[0011] Step 3, respectively taking the hollow CeO2 powder and dopamine hydrochloride in the ratio of (10-100 mg): (5-200 mg): (5-200 mL) and adding a Tris buffer solution with a concentration of 0.27-6 mg / mL, stirring evenly, centrifuging, washing and vacuum drying in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0012] Step 4: Place CeO2@PDA in a tube furnace, and heat it from room temperature to 350-800°C at a heating rate of 2°C / min in an argon atmosphere, and keep it for 1-5h to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material.

[0013] Furthermore, the Cu2O in step 1 is prepared by the following method:

[0014] Step 1.1, mixing ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution;

[0015] Step 1.2, in a water bath at 50-80°C, first dissolve 1-4 g of Cu2SO4·5H2O in 100-300 mL of the ethanol solution prepared in step 1.1, then add 10-30 mL of ethylene glycol, stir for 40 min, then add 5-20 mL of 2M NaOH solution dropwise, stir for 40 min, to obtain a black solution;

[0016] Step 1.3, add 3-10 g of ascorbic acid powder into 30-50 mL of ultrapure water and stir for 40 min to obtain an ascorbic acid solution;

[0017] Step 1.4: Add ascorbic acid solution dropwise to the black solution to obtain a brick-red solution. Stir the solution at room temperature for 40 min, let it stand for 3 h, and then filter, wash and vacuum dry in sequence to obtain brick-red Cu2O.

[0018] Furthermore, the stirring in step 1 is carried out using a magnetic stirrer for 30 to 90 minutes.

[0019] Furthermore, the stirring time of step 2 is 1 hour, and the static aging time is 12 hours.

[0020] Furthermore, the washing in step 2 is performed by alternately washing with deionized water and anhydrous ethanol for 3 times.

[0021] Furthermore, the vacuum drying in step 2 is performed in a vacuum drying oven at 60° C. for 12 hours.

[0022] Furthermore, the Tris buffer solution in step 3 is prepared by the following method:

[0023] First, 0.06-0.24 g of trimethyldolamine methane Tris is added to 40-220 mL of deionized water, stirred for 30-120 min, and then the pH is adjusted to 8.5 with a 0.1-0.5 M hydrochloric acid solution to obtain a Tris buffer solution.

[0024] A carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material.

[0025] Application of carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material in lithium-sulfur battery separator.

[0026] Furthermore, the application of the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material in a lithium-sulfur battery separator comprises the following steps:

[0027] The carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF were weighed and mixed and ground according to the mass ratio of (7-8):(1-2):1, and NMP was added dropwise and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator and dried to obtain a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC modified lithium-sulfur battery separator.

[0028] Compared with the prior art, the present invention has the following technical effects:

[0029] The present invention is based on the Pearson hard-soft acid-base theory. Cu2O is first used as a template and sodium thiosulfate Na2S2O3 is used as an etchant to synthesize cerium oxide CeO2 with a spherical shell structure. A layer of polydopamine is then coated on the surface of the cerium oxide. Then, a simple carbonization treatment is performed to obtain a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material. The composite material has the advantages of low cost, short process cycle, simplicity and ease of operation, and a wide range of applications.

[0030] The carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material prepared by the present invention has abundant oxygen vacancies, improves the transfer of electrons and ions, effectively modifies the surface electronic structure, produces a larger interlayer spacing, and simultaneously utilizes the abundant localized electrons, and the vacancies can be used as adsorption and catalytic sites for the fixation and conversion of various intermediates, thereby enhancing the charge storage power; moreover, the coated carbon shell structure improves the overall conductivity of the composite material, the hollow sphere shell structure can provide more adsorption and catalytic sites, and inhibits the shuttling of polysulfides through a physical barrier. In short, the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material plays a multi-effect synergistic role, can effectively inhibit the shuttling of polysulfides and induce the uniform deposition of Li2S, thereby effectively improving the reaction kinetics of lithium-sulfur batteries, so that the Li-S battery achieves a stable long cycle life cycle, excellent high rate performance and good electrocatalytic activity.

[0031] The Li-S battery assembled by the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material modified diaphragm prepared by the present invention has a capacity of up to 1381.2 mAh·g when the current density is 0.2, 0.5, 1, 2, 3 and 5C respectively. -1 、1150.4mAh·g -1 、972.4mAh·g -1 、858.0mAh·g -1 、794.5mAh·g -1 and 728.8mAh·g -1 In addition, at 0.2C, after 400 cycles, it still maintained 1074.3mAh·g -1 The ultra-high specific capacity of H-CeO2@C-NC was achieved, with a capacity retention rate of 82.40%. At 2C, after 1430 cycles, the capacity decay of H-CeO2@C-NC per cycle was only 0.015%, showing excellent reversibility and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the XRD pattern of the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material synthesized in Example 1 of the present invention;

[0033] Figure 2 This is an EPR graph of the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material synthesized in Example 1 of the present invention;

[0034] Figure 3 This is a SEM image of the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material synthesized in Example 1 of the present invention;

[0035] Figure 4 This is a TEM image of the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material synthesized in Example 1 of the present invention;

[0036] Figure 5 The rate performance diagram of Li-S batteries assembled with H-CeO2 modified diaphragm, CeO2 modified diaphragm, commercial polypropylene diaphragm and the diaphragm modified with the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material synthesized in Example 1 of the present invention;

[0037] Figure 6 The cycling performance diagram of Li-S battery assembled with H-CeO2 modified diaphragm, CeO2 modified diaphragm, commercial polypropylene diaphragm and H-CeO2@C-NC composite material modified diaphragm with oxygen vacancy in carbon coating synthesized in Example 1 of the present invention at a current density of 0.2C;

[0038] Figure 7 The cycling performance diagram of Li-S battery assembled with H-CeO2 modified separator, CeO2 modified separator, commercial polypropylene separator and H-CeO2@C-NC composite material modified separator with carbon-coated oxygen-rich vacancy hollow sphere synthesized in Example 1 of the present invention at 1C current density;

[0039] Figure 8 The Li-S battery assembled with H-CeO2 modified membrane, CeO2 modified membrane, commercial polypropylene membrane and the membrane modified with the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material synthesized in Example 1 of the present invention has a high conductivity at 0.1 mV s -1 CV curves at a rate of . DETAILED DESCRIPTION

[0040] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0041] Example 1

[0042] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 70° C., 2 g of Cu2SO4·5H2O is first dissolved in 240 mL of ethanol solution, and then 20 mL of ethylene glycol is added, stirred for 40 min, and then 10 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 6 g of ascorbic acid powder is added to 30 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0043] Step 2: Dissolve 20 g of polyvinyl pyrrolidone in 600 mL of 50% ethanol solution, add 300 mg of CeCl3·7H2O, and after it is dissolved, add 500 mg of Cu2O, stir at room temperature with a magnetic stirrer for 60 min to obtain a brick red solution;

[0044] Step 3, add 200 mL of 1 M sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution, stir at room temperature for 1 hour, then stand and age for 12 hours, then centrifuge to separate the solid product, wash the solid product alternately with deionized water and anhydrous ethanol for 3 times, and finally put it into a vacuum drying oven at 60°C and dry it for 12 hours to obtain a light yellow hollow CeO2 powder;

[0045] Step 4: first add 0.06 g of trimethyldolamine methane Tris into 40 mL of deionized water, stir for 90 min, and then adjust the pH to 8.5 with a 0.1 M hydrochloric acid solution to obtain a Tris buffer solution;

[0046] Step 5: Take the hollow CeO2 powder and dopamine hydrochloride in a ratio of 100 mg: 100 mg: 100 mL, add Tris buffer solution, stir for 12 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0047] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 600°C at a heating rate of 2°C / min in an argon atmosphere, and keeping the temperature for 4 hours to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0048] Step 7: Weigh the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 7:2:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0049] like Figure 1 As shown, the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material prepared in the example matches well with the characteristic peaks of typical CeO2 (PDF#43-1002), and its characteristic peaks slightly shift to small angles compared with H-CeO2, which indicates that the introduction of oxygen vacancies leads to the expansion of the lattice. The generation of oxygen vacancies leads to a larger atomic structure, which further leads to the expansion of the lattice spacing.

[0050] like Figure 2 As shown, at g = 2.003, the strongest oxygen vacancy signal is displayed, proving that it exposes more oxygen vacancy defects.

[0051] like Figure 3 As shown, the scanning electron microscope image of the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material prepared in Example 1 shows uniformly distributed monodisperse nanospheres.

[0052] like Figure 4 As shown, the average size of the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material prepared in Example 1 is about 500-700nm, and the sample presents a hollow structure with a uniform shell thickness of about 40-100nm and an inner cavity diameter of about 400nm. The oxygen-vacancy-rich CeO2 and N-doped carbon shell provide efficient active sites for the chemical absorption and catalytic conversion of polysulfides, inhibiting the "shuttle effect".

[0053] MWCNTs / S was used as the positive electrode, metallic lithium was used as the negative electrode, 1.0M LiTFSI in DME:DOL=1:1Vol%with 1.0%LiNO3 solution was used as the electrolyte, commercial polypropylene diaphragm, H-CeO2 modified diaphragm, CeO2 modified diaphragm and carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material modified diaphragm prepared in Example 1 were used as lithium-sulfur battery diaphragms, and lithium-sulfur batteries were assembled in a glove box filled with argon gas. The results of the electrochemical performance test are as follows:

[0054] like Figure 5As shown in Figure 2, the Li-S battery assembled with the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite modified separator has a capacity of up to 1381.2 mAh g at current densities of 0.2, 0.5, 1, 2, 3, and 5 C, respectively. -1 、1150.4mAh·g -1 、972.4mAh·g -1 、858.0mAh·g -1 、794.5mAh·g -1 and 728.8mAh·g -1 , which is significantly better than the capacity of Li-S batteries assembled by H-CeO2 modified separator, CeO2 modified separator and commercial polypropylene separator under the same conditions.

[0055] like Figure 6 and Figure 7 The figure shows the long-term cycling performance of the four batteries at current densities of 0.2 and 2C, respectively. Among them, the Li-S battery assembled with a separator modified by a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material maintains 1074.3 mAh g after 400 cycles at 0.2C. -1 The ultra-high specific capacity achieved a capacity retention rate of 82.40%; after 1430 cycles at 2C, the capacity decay of H-CeO2@C-NC per cycle was only 0.015%, showing excellent reversibility and cycle stability, which is significantly better than the other three batteries.

[0056] like Figure 8 As shown in the figure, the two reduction peaks at ∼2.4 V (peak I) and ∼2.1 V (peak II) are attributed to the reduction of S8 to soluble Li2S4 first and then to insoluble Li2S. In the anodic scan, the oxidation peak at ∼2.3 V (peak III) is attributed to the oxidation of Li2S to soluble Li2S4. x (4≤x≤8), and finally oxidized to sulfur; it can be seen that compared with the Li-S batteries assembled with H-CeO2 modified membrane, CeO2 modified membrane and commercial polypropylene membrane, the redox signal of the Li-S battery assembled with carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material modified membrane appears earlier and stronger, and has more prominent redox reaction kinetics.

[0057] Example 2

[0058] Step 1, ultrapure water and anhydrous ethanol are mixed according to a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 70° C., 1.5 g of Cu2SO4·5H2O is first dissolved in 100 mL of ethanol solution, and then 10 mL of ethylene glycol is added, stirred for 40 min, and then 5 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 3 g of ascorbic acid powder is added to 30 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0059] Step 2: Dissolve 30 g of polyvinyl pyrrolidone in 600 mL of 50% ethanol solution, add 300 mg of CeCl3·7H2O, and after it is dissolved, add 300 mg of Cu2O, stir at room temperature with a magnetic stirrer for 90 min to obtain a brick red solution;

[0060] Step 3, add 200 mL of 1 M sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution, stir at room temperature for 1 hour, then stand and age for 12 hours, then centrifuge to separate the solid product, wash the solid product alternately with deionized water and anhydrous ethanol for 3 times, and finally put it into a vacuum drying oven at 60°C and dry it for 12 hours to obtain a light yellow hollow CeO2 powder;

[0061] Step 4: first add 0.24 g of trimethyldolamine methane Tris into 220 mL of deionized water, stir for 30 min, and then adjust the pH to 8.5 with a 0.2 M hydrochloric acid solution to obtain a Tris buffer solution;

[0062] Step 5: Take hollow CeO2 powder and dopamine hydrochloride in a ratio of 100 mg: 200 mg: 200 mL, add Tris buffer solution, stir for 24 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0063] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 500°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 4 hours to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0064] Step 7: Weigh the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 8:1:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0065] Example 3

[0066] Step 1, ultrapure water and anhydrous ethanol are mixed according to a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 80° C., 2.5 g of Cu2SO4·5H2O is first dissolved in 200 mL of ethanol solution, and then 15 mL of ethylene glycol is added, stirred for 40 min, and then 7.5 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 5 g of ascorbic acid powder is added to 40 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0067] Step 2: Dissolve 30 g of polyvinyl pyrrolidone in 700 mL of 50% ethanol solution, add 400 mg of CeCl3·7H2O, and after it is dissolved, add 600 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0068] Step 3, add 200 mL of 1 M sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution, stir at room temperature for 1 hour, then stand and age for 12 hours, then centrifuge to separate the solid product, wash the solid product alternately with deionized water and anhydrous ethanol for 3 times, and finally put it into a vacuum drying oven at 60°C and dry it for 12 hours to obtain a light yellow hollow CeO2 powder;

[0069] Step 4: first add 0.15 g of trimethyldolamine methane Tris into 130 mL of deionized water, stir for 60 min, and then adjust the pH to 8.5 with a 0.3 M hydrochloric acid solution to obtain a Tris buffer solution;

[0070] Step 5: Take the hollow CeO2 powder and dopamine hydrochloride in a ratio of 60 mg: 100 mg: 200 mL, add Tris buffer solution, stir for 6 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0071] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 350°C at a heating rate of 2°C / min in an argon atmosphere, and keeping the temperature for 2h to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0072] Step 7: Weigh the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 8:1:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0073] Example 4

[0074] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 60° C., 1 g of Cu2SO4·5H2O is first dissolved in 100 mL of ethanol solution, and then 10 mL of ethylene glycol is added, stirred for 40 min, and then 10 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 8 g of ascorbic acid powder is added to 30 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0075] Step 2: Dissolve 15 g of polyvinyl pyrrolidone in 600 mL of 50% ethanol solution, add 400 mg of CeCl3·7H2O, and after it is dissolved, add 300 mg of Cu2O, stir at room temperature with a magnetic stirrer for 30 min to obtain a brick red solution;

[0076] Step 3, add 200 mL of 1 M sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution, stir at room temperature for 1 hour, then stand and age for 12 hours, then centrifuge to separate the solid product, wash the solid product alternately with deionized water and anhydrous ethanol for 3 times, and finally put it into a vacuum drying oven at 60°C and dry it for 12 hours to obtain a light yellow hollow CeO2 powder;

[0077] Step 4: first add 0.1 g of trimethylolamine methane Tris into 80 mL of deionized water, stir for 100 min, and then adjust the pH to 8.5 with a 0.4 M hydrochloric acid solution to obtain a Tris buffer solution;

[0078] Step 5: Take hollow CeO2 powder and dopamine hydrochloride in a ratio of 500 mg: 200 mg: 100 mL, add Tris buffer solution, stir for 3 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0079] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 600°C at a heating rate of 2°C / min in an argon atmosphere, and keeping the temperature for 4 hours to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0080] Step 7: Weigh the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 7:2:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0081] Example 5

[0082] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 60° C., 3 g of Cu2SO4·5H2O is first dissolved in 200 mL of ethanol solution, and then 20 mL of ethylene glycol is added, stirred for 40 min, and then 15 mL of 2M NaOH solution is added dropwise, stirred for 40 min, to obtain a black solution; 10 g of ascorbic acid powder is added to 40 mL of ultrapure water, stirred for 40 min, to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0083] Step 2: Dissolve 20 g of polyvinyl pyrrolidone in 800 mL of 50% ethanol solution, add 450 mg of CeCl3·7H2O, and after it is dissolved, add 500 mg of Cu2O, stir at room temperature with a magnetic stirrer for 60 min to obtain a brick red solution;

[0084] Step 3, add 200 mL of 1 M sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution, stir at room temperature for 1 hour, then stand and age for 12 hours, then centrifuge to separate the solid product, wash the solid product alternately with deionized water and anhydrous ethanol for 3 times, and finally put it into a vacuum drying oven at 60°C and dry it for 12 hours to obtain a light yellow hollow CeO2 powder;

[0085] Step 4: first add 0.2 g of trimethyldolamine methane Tris into 180 mL of deionized water, stir for 120 min, and then adjust the pH to 8.5 with a 0.5 M hydrochloric acid solution to obtain a Tris buffer solution;

[0086] Step 5: Take hollow CeO2 powder and dopamine hydrochloride in a ratio of 100 mg: 50 mg: 50 mL, add Tris buffer solution, stir for 12 h, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0087] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 500°C at a heating rate of 2°C / min under an argon atmosphere, and keeping the temperature for 5 hours to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0088] Step 7: Weigh the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF in a mass ratio of 7:1:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0089] Example 6

[0090] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; in a water bath at 70°C, 3.5 g of Cu2SO4·5H2O is first dissolved in 250 mL of ethanol solution, 30 mL of ethylene glycol is added, and the mixture is stirred for 40 min, and then 16 mL of 2M NaOH solution is added dropwise, and the mixture is stirred for 40 min to obtain a black solution; 10 g of ascorbic acid powder is added to 45 mL of ultrapure water, and the mixture is stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0091] Step 2: Dissolve 10 g of polyvinyl pyrrolidone in 650 mL of 50% ethanol solution, add 500 mg of CeCl3·7H2O, and after it is dissolved, add 500 mg of Cu2O, stir at room temperature with a magnetic stirrer for 70 min to obtain a brick red solution;

[0092] Step 3, add 300 mL of 1 M sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution, stir at room temperature for 1 hour, then stand and age for 12 hours, then centrifuge to separate the solid product, wash the solid product alternately with deionized water and anhydrous ethanol for 3 times, and finally put it into a vacuum drying oven at 60°C and dry it for 12 hours to obtain a light yellow hollow CeO2 powder;

[0093] Step 4: first add 0.06 g of trimethylolamine methane Tris into 220 mL of deionized water, stir for 40 min, and then adjust the pH to 8.5 with a 0.4 M hydrochloric acid solution to obtain a Tris buffer solution;

[0094] Step 5: Take hollow CeO2 powder and dopamine hydrochloride in a ratio of 80 mg: 200 mg: 200 mL, add Tris buffer solution, stir for 9 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0095] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 700°C at a heating rate of 2°C / min in an argon atmosphere, and keeping the temperature for 3 hours to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0096] Step 7: Weigh the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 7.5:1.5:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0097] Example 7

[0098] Step 1, ultrapure water and anhydrous ethanol are mixed according to a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 80° C., 4 g of Cu2SO4·5H2O is first dissolved in 300 mL of ethanol solution, and then 30 mL of ethylene glycol is added, stirred for 40 min, and then 18 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 9 g of ascorbic acid powder is added to 35 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0099] Step 2: Dissolve 30 g of polyvinyl pyrrolidone in 700 mL of 50% ethanol solution, add 500 mg of CeCl3·7H2O, and after it is dissolved, add 550 mg of Cu2O, stir at room temperature with a magnetic stirrer for 80 min to obtain a brick red solution;

[0100] Step 3, 400 mL of 1 M sodium thiosulfate solution was added dropwise to the brick-red solution to obtain a light yellow solution, which was stirred at room temperature for 1 h, then aged for 12 h, and then centrifuged to separate the solid product, and the solid product was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C. and dried for 12 h to obtain a light yellow hollow CeO2 powder;

[0101] Step 4: first add 0.24 g of trimethyldolamine methane Tris into 40 mL of deionized water, stir for 50 min, and then adjust the pH to 8.5 with a 0.3 M hydrochloric acid solution to obtain a Tris buffer solution;

[0102] Step 5: Take hollow CeO2 powder and dopamine hydrochloride in a ratio of 70 mg: 140 mg: 200 mL, add Tris buffer solution, stir for 8 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0103] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 600°C at a heating rate of 2°C / min in an argon atmosphere, and keeping the temperature for 4 hours to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0104] Step 7: Weigh the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 7:2:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0105] Example 8

[0106] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 60° C., 1 g of Cu2SO4·5H2O is first dissolved in 150 mL of ethanol solution, and then 15 mL of ethylene glycol is added, stirred for 40 min, and then 15 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 6 g of ascorbic acid powder is added to 50 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0107] Step 2: Dissolve 15 g of polyvinyl pyrrolidone in 650 mL of 50% ethanol solution, add 450 mg of CeCl3·7H2O, and after it is dissolved, add 450 mg of Cu2O, stir at room temperature with a magnetic stirrer for 40 min to obtain a brick red solution;

[0108] Step 3, 400 mL of 1 M sodium thiosulfate solution was added dropwise to the brick-red solution to obtain a light yellow solution, which was stirred at room temperature for 1 h, then aged for 12 h, and then centrifuged to separate the solid product, and the solid product was washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C. and dried for 12 h to obtain a light yellow hollow CeO2 powder;

[0109] Step 4: first add 0.21 g of trimethyldolamine methane Tris into 70 mL of deionized water, stir for 70 min, and then adjust the pH to 8.5 with a 0.2 M hydrochloric acid solution to obtain a Tris buffer solution;

[0110] Step 5: Take hollow CeO2 powder and dopamine hydrochloride in a ratio of 50 mg: 200 mg: 200 mL, add Tris buffer solution, stir for 7 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0111] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 650°C at a heating rate of 2°C / min in an argon atmosphere, and keeping the temperature for 3.5h to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0112] Step 7: Weigh the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 8:1:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0113] Example 9

[0114] Step 1, ultrapure water and anhydrous ethanol are mixed according to a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 50° C., 2.5 g of Cu2SO4·5H2O is first dissolved in 200 mL of ethanol solution, and then 20 mL of ethylene glycol is added, stirred for 40 min, and then 12.5 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 6.5 g of ascorbic acid powder is added to 45 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0115] Step 2: Dissolve 25 g of polyvinyl pyrrolidone in 650 mL of 50% ethanol solution, add 500 mg of CeCl3·7H2O, and after it is dissolved, add 600 mg of Cu2O, stir at room temperature with a magnetic stirrer for 50 min to obtain a brick red solution;

[0116] Step 3, add 300 mL of 1 M sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution, stir at room temperature for 1 hour, then stand and age for 12 hours, then centrifuge to separate the solid product, wash the solid product alternately with deionized water and anhydrous ethanol for 3 times, and finally put it into a vacuum drying oven at 60°C and dry it for 12 hours to obtain a light yellow hollow CeO2 powder;

[0117] Step 4: first add 0.12 g of trimethyldolamine methane Tris into 60 mL of deionized water, stir for 80 min, and then adjust the pH to 8.5 with a 0.5 M hydrochloric acid solution to obtain a Tris buffer solution;

[0118] Step 5: Take the hollow CeO2 powder and dopamine hydrochloride in a ratio of 40 mg: 100 mg: 100 mL, add Tris buffer solution, stir for 3 to 24 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0119] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 800°C at a heating rate of 2°C / min in an argon atmosphere, and keeping the temperature for 1 hour to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0120] Step 7: Weigh the carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 8:1:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

[0121] Example 10

[0122] Step 1, ultrapure water and anhydrous ethanol are mixed in a volume ratio of 2:1 to obtain an ethanol solution; under a water bath condition of 80° C., 3 g of Cu2SO4·5H2O is first dissolved in 250 mL of ethanol solution, and then 30 mL of ethylene glycol is added, stirred for 40 min, and then 20 mL of 2M NaOH solution is added dropwise, and stirred for 40 min to obtain a black solution; 10 g of ascorbic acid powder is added to 50 mL of ultrapure water, and stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution is added dropwise to the black solution to obtain a brick-red solution, which is stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu2O;

[0123] Step 2: Dissolve 40 g of polyvinyl pyrrolidone in 600 mL of 50% ethanol solution, add 600 mg of CeCl3·7H2O, and after it is dissolved, add 550 mg of Cu2O, stir at room temperature with a magnetic stirrer for 75 min to obtain a brick red solution;

[0124] Step 3, add 300 mL of 1 M sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution, stir at room temperature for 1 hour, then stand and age for 12 hours, then centrifuge to separate the solid product, wash the solid product alternately with deionized water and anhydrous ethanol for 3 times, and finally put it into a vacuum drying oven at 60°C and dry it for 12 hours to obtain a light yellow hollow CeO2 powder;

[0125] Step 4: first add 0.2 g of trimethylolamine methane Tris into 50 mL of deionized water, stir for 110 min, and then adjust the pH to 8.5 with a 0.1 M hydrochloric acid solution to obtain a Tris buffer solution;

[0126] Step 5: Take hollow CeO2 powder and dopamine hydrochloride in a ratio of 50 mg: 150 mg: 150 mL, add Tris buffer solution, stir for 3 to 24 hours, centrifuge, wash and vacuum dry in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA;

[0127] Step 6, placing CeO2@PDA in a tube furnace, heating from room temperature to 750°C at a heating rate of 2°C / min in an argon atmosphere, and keeping the temperature for 2.5h to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material;

[0128] Step 7: Weigh the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF according to a mass ratio of 7:2:1, mix and grind them, add 10 drops of NMP, stir to obtain a uniform slurry, and evenly coat the slurry on the surface of a commercial polypropylene diaphragm, dry it, and obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC modified lithium-sulfur battery diaphragm.

Claims

1. A method for preparing a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material, characterized in that: The steps include: Step 1: Dissolve 10-40 g of polyvinyl pyrrolidone in 600-800 mL of 50% ethanol solution, add 300-600 mg of CeCl3·7H2O, and after it is dissolved, add 300-600 mg of Cu2O, stir at room temperature, and obtain a brick red solution; Step 2, 200-400 mL of 1M sodium thiosulfate solution was added dropwise to the brick-red solution to obtain a light yellow solution, which was stirred at room temperature, and then allowed to stand for aging, centrifuged, washed and vacuum dried in sequence to obtain a light yellow hollow CeO2 powder; Step 3, respectively taking the hollow CeO2 powder and dopamine hydrochloride in the ratio of (10-100 mg): (5-200 mg): (5-200 mL) and adding a Tris buffer solution with a concentration of 0.27-6 mg / mL, stirring evenly, centrifuging, washing and vacuum drying in sequence to obtain a polydopamine-coated CeO2 composite material CeO2@PDA; Step 4: Place CeO2@PDA in a tube furnace, and heat it from room temperature to 350-800°C at a heating rate of 2°C / min in an argon atmosphere, and keep it for 1-5h to obtain a carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material.

2. The method for preparing the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material according to claim 1, characterized in that: The Cu2O in step 1 is prepared by the following method: Step 1.1, mixing ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; Step 1.2, in a water bath at 50-80°C, first dissolve 1-4 g of Cu2SO4·5H2O in 100-300 mL of the ethanol solution prepared in step 1.1, then add 10-30 mL of ethylene glycol, stir for 40 min, then add 5-20 mL of 2M NaOH solution dropwise, stir for 40 min, to obtain a black solution; Step 1.3, add 3-10 g of ascorbic acid powder into 30-50 mL of ultrapure water and stir for 40 min to obtain an ascorbic acid solution; Step 1.4: Add ascorbic acid solution dropwise to the black solution to obtain a brick-red solution. Stir the solution at room temperature for 40 min, let it stand for 3 h, and then filter, wash and vacuum dry in sequence to obtain brick-red Cu2O.

3. The method for preparing the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material according to claim 1, characterized in that: The stirring in step 1 is carried out by using a magnetic stirrer for 30 to 90 minutes.

4. The method for preparing the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material according to claim 1, characterized in that: The stirring time of step 2 is 1 hour, and the static aging time is 12 hours.

5. The method for preparing the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material according to claim 1, characterized in that: The washing in step 2 is performed by alternately washing with deionized water and anhydrous ethanol for 3 times.

6. The method for preparing the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material according to claim 1, characterized in that: The vacuum drying in step 2 is carried out in a vacuum drying oven at 60° C. for 12 h.

7. The method for preparing the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material according to claim 1, characterized in that: The Tris buffer solution in step 3 is prepared by the following method: First, 0.06-0.24 g of trimethyldolamine methane Tris is added to 40-220 mL of deionized water, stirred for 30-120 min, and then the pH is adjusted to 8.5 with a 0.1-0.5 M hydrochloric acid solution to obtain a Tris buffer solution.

8. A carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material prepared by the method of claim 1.

9. Use of the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material as claimed in claim 8 in a lithium-sulfur battery separator.

10. The use of the carbon-coated oxygen-rich hollow sphere H-CeO2@C-NC composite material in a lithium-sulfur battery separator according to claim 9, characterized in that: The steps include: The carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC composite material, acetylene black and PVDF were weighed and mixed and ground according to the mass ratio of (7-8):(1-2):1, and NMP was added dropwise and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator and dried to obtain a carbon-coated oxygen-rich vacancy hollow sphere H-CeO2@C-NC modified lithium-sulfur battery separator.

Citation Information

Cited By

  • Targeted drug delivery platform based on mesoporous cerium oxide nanoparticles as well as preparation method and application of targeted drug delivery platform

    CN120078725A